2006
DOI: 10.1002/ejoc.200600220
|View full text |Cite
|
Sign up to set email alerts
|

The Stereochemistry of Allenic Enol Tautomerism – Independent Generation and Reactivity of the Enolates

Abstract: A priori, allenic enolates as reaction intermediates may be protonated to afford (Z)‐ or (E)‐α,β‐unsaturated carbonyl products. The allenic enolates are tautomeric with α‐vinylcarbanions. The literature on the behavior of these species on protonation is highly varied both in stereochemical outcome and in mechanistic interpretation. The current study has provided an independent mode of generation of the allenic enolates and has investigated the reaction stereochemistry of protonation to afford the stereoisomeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
29
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 26 publications
6
29
0
1
Order By: Relevance
“…The tendency of the transformation into Z isomers was found to depend on the electronic nature of the aryl substituent at the propargyl position ( Table 2, On the basis of several experiments mentioned below, the unprecedented Z selectivity can be accounted for by the characteristic bulkiness and acidity of the heteropoly compounds. First, monitoring the reaction of 1 a with Ag 3 [PMo 12 O 40 ]·n H 2 O by 1 H NMR spectroscopy revealed that (Z)-2 a formed about ten times more quickly than (E)-2 a (Figure 1). Although a large amount of the dimer 3 was generated at the beginning of the reaction, 3 was found to react with Ag 3 [PMo 12 O 40 ]·n H 2 O under the same conditions to preferentially afford (Z)-2 a [(Z)-2 a/(E)-2 a % 10:1].…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…The tendency of the transformation into Z isomers was found to depend on the electronic nature of the aryl substituent at the propargyl position ( Table 2, On the basis of several experiments mentioned below, the unprecedented Z selectivity can be accounted for by the characteristic bulkiness and acidity of the heteropoly compounds. First, monitoring the reaction of 1 a with Ag 3 [PMo 12 O 40 ]·n H 2 O by 1 H NMR spectroscopy revealed that (Z)-2 a formed about ten times more quickly than (E)-2 a (Figure 1). Although a large amount of the dimer 3 was generated at the beginning of the reaction, 3 was found to react with Ag 3 [PMo 12 O 40 ]·n H 2 O under the same conditions to preferentially afford (Z)-2 a [(Z)-2 a/(E)-2 a % 10:1].…”
mentioning
confidence: 98%
“…First, monitoring the reaction of 1 a with Ag 3 [PMo 12 O 40 ]·n H 2 O by 1 H NMR spectroscopy revealed that (Z)-2 a formed about ten times more quickly than (E)-2 a (Figure 1). Although a large amount of the dimer 3 was generated at the beginning of the reaction, 3 was found to react with Ag 3 [PMo 12 O 40 ]·n H 2 O under the same conditions to preferentially afford (Z)-2 a [(Z)-2 a/(E)-2 a % 10:1]. [10] We also observed a similar selective formation of (Z)-2 a with Na 3 [PMo 12 O 40 ]·n H 2 O as the catalyst.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Among the various cations, a silver salt exhibited higher reactivity and Z selectivity (entries 2, and 5-7). The reaction of 1 a with Ag 3 [PMo 12 O 40 ]·n H 2 O in EtOAc gave (Z)-2 a in 66 % yield (NMR spectroscopy); furthermore, the use of the same silver salt in acetone dramatically improved both the yield and the stereoselectivity (entries 7-9). [9] Under the optimal reaction conditions, we subsequently examined the reactions of a series of secondary propargyl alcohols 1 b-g ( Table 2).…”
mentioning
confidence: 99%
“…[7] One of the most common heteropoly acids is the Keggin-type compounds with the general formula H n [XM 12 O 40 ] in which X is the central heteroatom and M is the addenda atom. They possess a strong acidity and redox properties, both of which can be tuned by simply changing the cationic moiety and the polyanion chemical composition.…”
mentioning
confidence: 99%